Reformulation of Policy on the Dualistic Structure of Non-Litigious Sharia Financial Dispute Resolution Bodies in Indonesia: A Comparative Study with Malaysia and Brunei Darussalam - Indah Fatmawati; Leli Joko Suryono (Al-Huquq: Journal of Indonesian Islamic Economic Law, 2026)
Non-litigation dispute resolution in the Indonesian Islamic financial sector demonstrates institutional dualism through the coexistence of the National Sharia Arbitration Board (BASYARNAS) and the Alternative Dispute Resolution Institution for the Financial Services Sector (LAPS-SJK). Both institutions operate under different legal foundations, institutional orientations, and jurisdictions, yet each maintains authority over Islamic financial disputes, creating overlapping competencies and uncertainty about dispute-settlement forums. This study aims to examine the structure of institutional dualism between BASYARNAS and LAPS-SJK and formulate a policy reform model through comparative analysis with Malaysia and Brunei Darussalam. The study employs normative legal research, drawing on statutory, conceptual, and comparative approaches. Secondary data, consisting of primary, secondary, and tertiary legal materials, were collected through library research and analyzed qualitatively through legal interpretation, regulatory synchronization, and comparative analysis. The findings indicate that the central issue does not lie in the existence of multiple institutions but in the absence of clear competency boundaries. Malaysia adopts administrative integration through the Financial Markets Ombudsman Service (FMOS), while Brunei Darussalam applies coordinated dispute settlement through the Brunei Darussalam Arbitration Center (BDAC). Based on these findings, this study proposes a policy reform based on the differentiation of competences between BASYARNAS and LAPS-SJK, supported by a one-gate dispute resolution mechanism to strengthen forum certainty without eliminating the distinctive character of dispute resolution founded on Sharia principles. Academically, this study recommends further research on regulatory design, inter-institutional referral mechanisms, and the effectiveness of implementing one-gate dispute resolution in resolving Sharia financial disputes